Influence of HLA class I and HLA-KIR compound genotypes on HIV-2 infection and markers of disease progression in a Manjako community in West Africa. - Yindom, L; Leligdowicz, A; Martin, M; Gao, X; Qi, Y; Zaman, S; van der Loeff, MS; van Tienen, C; Jaye, A; Aveika, A; Worwui, A; Diatta, M; et al. (2010)
Overall, the time to AIDS after HIV-2 infection is longer than with HIV-1, and many individuals infected with HIV-2 virus remain healthy throughout their lives. Multiple HLA and KIR gene products have been implicated in the control of HIV-1, but the effect of variation at these loci on HIV-2 disease is unknown. We show here for the first time that HLA-B*1503 is associated significantly with poor prognosis after HIV-2 infection and that HLA-B*0801 is associated with susceptibility to infection. Interestingly, previous data indicate that HLA-B*1503 is associated with low viral loads in HIV-1 clade B infection but has no significant effect on viral load in clade C infection. In general, alleles strongly associated with HIV-1 disease showed no effect in HIV-2 disease. These data emphasize the unique nature of the effects of HLA and HLA/KIR combinations on HIV-2 immune responses relative to HIV-1, which could be related to their distinct clinical course.